2021
DOI: 10.3389/fpsyg.2021.640955
|View full text |Cite|
|
Sign up to set email alerts
|

Illness Perceptions of COVID-19 in Europe: Predictors, Impacts and Temporal Evolution

Abstract: Objective: Illness perceptions (IP) are important predictors of emotional and behavioral responses in many diseases. The current study aims to investigate the COVID-19-related IP throughout Europe. The specific goals are to understand the temporal development, identify predictors (within demographics and contact with COVID-19) and examine the impacts of IP on perceived stress and preventive behaviors.Methods: This was a time-series-cross-section study of 7,032 participants from 16 European countries using mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…According to the common-sense model of self regulation (CSM), a theoretical framework enabling understanding of how people cope with threats to their health, such illness perceptions are influenced by situational stimuli such as symptoms, health information and patient’s knowledge (17–19). The individual illness perception was shown to influence disease coping, adjustment to adverse life events or chronic conditions and compliance with prevention, treatment and rehabilitation (20,21), also in context of acute COVID-19 (2224). Finally, severe illness perception including the emotional response, concerns and consequence components was found associated with anxiety, depression and stress both in the general population and in COVID-19 patients (2528).…”
Section: Introductionmentioning
confidence: 99%
“…According to the common-sense model of self regulation (CSM), a theoretical framework enabling understanding of how people cope with threats to their health, such illness perceptions are influenced by situational stimuli such as symptoms, health information and patient’s knowledge (17–19). The individual illness perception was shown to influence disease coping, adjustment to adverse life events or chronic conditions and compliance with prevention, treatment and rehabilitation (20,21), also in context of acute COVID-19 (2224). Finally, severe illness perception including the emotional response, concerns and consequence components was found associated with anxiety, depression and stress both in the general population and in COVID-19 patients (2528).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, perceptions of more severe consequences and possibilities for prevention, more concerns and worries about the illness, and a better understanding of the illness were positively related to the intention to and the actual engagement in preventive behaviors [ 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. Neto and colleagues [ 44 ] investigated the associations of illness representations about COVID-19 with non-pharmacological preventive behaviors and found that more concerns about COVID-19 and more perceived personal control about COVID-19 were related to more social distancing, handwashing, and self-isolation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a large-scale study of IP addresses associated with COVID-19 across Europe have been published. The authors analyzed the temporal development, identified predictors (within demographics and contact with COVID-19), and examined the impacts of IP on perceived stress and preventive behaviors (Dias Neto et al, 2021).…”
Section: Discussionmentioning
confidence: 99%